Spelling errors found in descriptive writing among seventh-graders of lower secondary school in Klaten district - Jayus Ngumarno; Erry Pranawa; Suhud Eko Yuwono; Septina Dyah Astuti; Sri Budiyono (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to investigate errors found among seventh-graders descriptive writing of SMP N 2 Trucuk, Klaten district, Indonesia. This study used a qualitative descriptive approach. Data was collected from the notes-taking techniques from which the seventh-graders produced errors in their descriptive writing. Data analysis qualitatively identified seventh-graders descriptive writing. The results showed that there were errors found in the form of writing capital letters use, writing compound words, prepositions [at, to, and from], and punctuation marks [.] Errors in using capital letters included in naming geography at the beginning of sentences, capital letters used in people's names, and writing capital letters in the middle of sentences. Combination of spelling errors. Errors in writing prepositions (at, to, and from). Error using punctuation.